PENGARUH LAGU “OKE GAS” SEBAGAI STRATEGI KOMUNIKASI POLITIK BERBASIS POP CULTURE TERHADAP ELEKTABILITAS PASANGAN PRABOWO-GIBRAN PADA PEMILU 2024 DI KECAMATAN TEMBALANG - Ari Sigit; Wijayanto Wijayanto (Journal of Politic and Government Studies, 2026)
The development of digital media has driven a transformation in political communication toward a more interactive approach closely tied to popular culture. In the 2024 Indonesian General Election, the Prabowo Subianto and Gibran Rakabuming Raka campaign leveraged the "Oke Gas" campaign song as a political communication instrument to reach young voters through social media. This study aims to measure and analyze the influence of the "Oke Gas" song as a pop culture-based political communication strategy on the electability of the Prabowo-Gibran ticket in Tembalang District, Semarang City. The study employed a quantitative explanatory approach using the Proportionate Stratified Random Sampling technique. Data were gathered from 423 respondents and analyzed using the Pearson correlation test, simple linear regression, and hypothesis testing with SPSS. Results indicated a positive and significant effect (R² = 0.547; t = 22.543; sig. 0.000), confirming that utilizing popular culture in digital campaigns can increase candidate recognition, interest, trust, and voting tendency—especially among young voters who are active social media users.